THEORETICAL AND PRACTICAL FUNDAMENTALS OF DEVELOPING THE CREATIVE ABILITY OF PRIMARY SCHOOL STUDENTS - Djurakulova Adolat Khalmuratovna; Tashbaeva Ogilshod Abduvakhidovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article is about the theoretical and practical foundations of developing the creative abilities of primary school students. Based on the above, we can conclude that the psychological aspect of the development of creative ability involves goal-oriented activities related to the identification of motivating motives, goals of creativity, specific features, as well as thinking operations, subjective analysis of logical processes underlying them.